2016
DOI: 10.3390/nano6100180
|View full text |Cite
|
Sign up to set email alerts
|

Probe Microscopic Studies of DNA Molecules on Carbon Nanotubes

Abstract: Hybrids of DNA and carbon nanotubes (CNTs) are promising nanobioconjugates for nanobiosensors, carriers for drug delivery, and other biological applications. In this review, nanoscopic characterization of DNA-CNT hybrids, in particular, characterization by scanning probe microscopy (SPM), is summarized. In many studies, topographical imaging by atomic force microscopy has been performed. However, some researchers have demonstrated advanced SPM operations in order to maximize its unique and valuable functions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 95 publications
0
9
0
Order By: Relevance
“…We first took advantage of the unique fluorescence quenching effect of SWNTs on the adsorbed fluorescently labelled DNA, which provided an effective way to quantify the amount of DNA molecules adsorbed onto the SWNT surfaces. Secondly, as DNA adsorption onto SWNT surfaces causes an increase in SWNT diameter [5, 15, 30], we utilized AFM to measure the dimensions of individual DNA-SWNT hybrids based on their cross-section values in the images. This approach allowed us to directly assess the effects of sonication on the DNA-SWNT hybridization process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We first took advantage of the unique fluorescence quenching effect of SWNTs on the adsorbed fluorescently labelled DNA, which provided an effective way to quantify the amount of DNA molecules adsorbed onto the SWNT surfaces. Secondly, as DNA adsorption onto SWNT surfaces causes an increase in SWNT diameter [5, 15, 30], we utilized AFM to measure the dimensions of individual DNA-SWNT hybrids based on their cross-section values in the images. This approach allowed us to directly assess the effects of sonication on the DNA-SWNT hybridization process.…”
Section: Resultsmentioning
confidence: 99%
“…Samples were sonicated using either a probe-type sonicator (VCX 130 630-0423: ϕ = 2 mm, 130W; Sonics & Materials Inc., Newtown USA) or a bath-type sonicator (80W; EOL80; Steady Ultrasonic Sdn. Bhd., Selangor Malaysia) [2830]. The different sonication conditions were as follows: (a) sonication at 60% maximum amplitude of the probe-type sonicator (P60), (b) sonication at 20% maximum amplitude of the probe-type sonicator (P20), (c) bath-type sonication (B), and (d) control (no sonication).…”
Section: Methodsmentioning
confidence: 99%
“…Carbon nanotubes (CNTs) are promising nanomaterials because of their extraordinary mechanical, electrical, and optical properties [ 1 , 2 , 3 , 4 ]. To apply CNTs to various applications such as nanodevices and nanobiodevices, preparing suspensions of CNTs is one of the primary techniques [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Evaluating DNA molecules is important for developing biological applications. Many authors have reported the physical and chemical characterizations of DNA-SWNT hybrids using microscopy [9][10][11] and spectroscopy [12][13][14][15][16][17]. Furthermore, theoretical models of the hybrid structures have been proposed by several authors [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%